Bone Formation Is Coupled to Resorption Via Suppression of Sclerostin Expression by Osteoclasts. (15th June 2017) - Koide, Masanori; Kobayashi, Yasuhiro; Yamashita, Teruhito; Uehara, Shunsuke; Nakamura, Midori; Hiraoka, B. Yukihiro; Ozaki, Yuki; Iimura, Tadahiro; Yasuda, Hisataka; Takahashi, Naoyuki; Udagawa, Nobuyuki
ABSTRACT: Bone formation is coupled to bone resorption throughout life. However, the coupling mechanisms are not fully elucidated. Using Tnfrsf11b ‐deficient ( OPG –/– ) mice, in which bone formation is clearly coupled to bone resorption, we found here that osteoclasts suppress the expression of sclerostin, a Wnt antagonist, thereby promoting bone formation. Wnt/β‐catenin signals were higher in OPG –/– and RANKL ‐transgenic mice with a low level of sclerostin. Conditioned medium from osteoclast cultures (Ocl‐CM) suppressed sclerostin expression in UMR106 cells and osteocyte cultures. In vitro experiments revealed that osteoclasts secreted leukemia inhibitory factor (LIF) and inhibited sclerostin expression. Anti‐RANKL antibodies, antiresorptive agents, suppressed LIF expression and increased sclerostin expression, thereby reducing bone formation in OPG –/– mice. Taken together, osteoclast‐derived LIF regulates bone turnover through sclerostin expression. Thus, LIF represents a target for improving the prolonged suppression of bone turnover by antiresorptive agents. © 2017 The Authors. Journal of Bone and Mineral Research Published by Wiley Periodicals Inc.